Stapled Versus Hand-Sewn Anastomosis in Colorectal Cancer Surgery : A comparative study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Introduction: In spite of long journey of intestinal anastomotic techniques surgeons still are not free from doubt about the leakage after colorectal anastomosis. In distal rectal anastomosis after cancer surgery it poses more risk due to poor colonic vascularity and reduced remaining tissue to nourish the anastomotic site. Exploration of surgical staplers has provided some procedural advantages and sense of security to surgeons as well as to patients in respect to sphincter saving and thereby improving quality of life. However, outcome measures of these devices should be made to see its efficacy over conventional hand-sewn technique because their cost play role in treatment plan. The result of such comparative study may help surgeons to counsel the patients. Objectives: To find out whether stapled anastomosis is safer than hand-sewn anastomosis in colon and rectal cancer surgery. methods: The quasi-experimental study was undertaken in the department of general and colorectal surgery, Bangabandu Sheikh Mujib Medical University hospital during Feb 2005 to June 2008. Total 100 patients were selected. 48 patients underwent Stapled and 52 underwent Hand-sewn anastomosis. The patients were treated and postoperatively managed by same colorectal surgeon. The outcome variables were time required for anastomoses, postoperative hospital stay and early and late complications in postoperative and follow-up period. Result and observation: The age, sex, socioeconomic status or co-morbidities did not show any statistical difference between two groups as in the hospital stay (p=.821). The time required for anastomosis showed strongly significant difference (18.17 min and 26.85 min; p=.000) in favor of stapling group. The hemorrhage from anastomotic line (p=1.00), anastomotic leakage (p=.413), ileus/ obstruction (p=.640) and wound dehiscence (p=.640) were much less in stapled group though they lack statistical power. All others except anastomotic stenosis (p=.514) showed almost similar results. Conclusion: Considering user perspective, time requirement and postoperative complications stapling technique appear to be safer and superior to hand-sewn technique though it demands statistical strengthening on large scale study. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 56-61